Necessity of DC Voltage Storage for Dynamic Voltage Restorer - Borakhade, Swapnil R.; Jawadekar, Anjali .U. (Asian Journal of Electrical Sciences, 2012)
Problems of voltage sags and swells and its severe impact on sensitive load is well known. To solve the problems custom power devices are used, one of those devices is DVR which is most efficient and effective modern custom power device used in power distribution network. DVR is a very effective series-compensation device for mitigating voltage sags. The mitigation capability of these devices is mainly limited by the energy storage capacity. This paper presents the application of DVR on power distribution systems for mitigation of voltage sag and swell. An adequate modeling and simulation of DVR, including controls in MATLAB, shows the flexibility and easiness of MATLAB environment in analyzing such compensating devices. DVR which is based on forced commutated voltage source converter has been proved suitable for the task of compensating voltage sags and swells. Simulation results are presented to illustrate and understand the performance of DVR in supporting load voltage under voltage sag or swell conditions and also to assimilate voltage capacity of DC storage unit of a DVR with transmission voltage, by considering various factors.